Aggression in group psychoanalytic psychotherapy : questionnaire development (GA-Ag) - Pavlović, Slavica, psihijatrica (Array, 2009)
Abstract: The aim of this study is developing of a questionnaire that observes aggression in group psychoanalytic psychotherapy and examines its factor structure. The questionnaire comprised of 160 statements in five-point Likert-type scale was developed through analysis of the content of aggressive communication among patients during group sessions. The questionnaire was applied on 253 patients that attended 40 small therapy groups in 9 cities in Croatia. All 20 group analysts are trained in the Institute for Group Analysis Zagreb. The patients were selected based on indications for group analysis. Two parallel questionnaire forms were designed of 80 items that were isolated through assessment of item discrimination and principal components analysis limited to five factors. A new, reliable and valid questionnaire that can be employed in group psychotherapy has been developed. The following has been isolated through factor analysis: 1. Difficulty in communication, 2. Distrust in the group therapist and the group, 3. Withdrawal from relationships and communication, 4. Low containing capacity, and 5. Mutual lack of understanding. This questionnaire can measure the level of difficulty in communication, distrust in the therapist and the group, passive aggression, containing capacity, lack of understanding among group participants and in the group as a whole